Effects of Lactate Transport Inhibition by AZD3965 in Muscle-Invasive Urothelial Bladder Cancer - Silva, Ana; Félix, Ana; Cerqueira, Mónica; Gonçalves, Céline S.; Sampaio-Marques, Belém; Longatto-Filho, Adhemar [UNESP]; Baltazar, Fátima; Afonso, Julieta (MDPI, 2023)
The Warburg Effect is characterized by high rates of glucose uptake and lactate production. Monocarboxylate transporters (MCTs) are crucial to avoid cellular acidosis by internal lactate accumulation, being largely overexpressed by cancer cells and associated with cancer aggressiveness. The MCT1-specific inhibitor AZD3965 has shown encouraging results in different cancer models. However, it has not been tested in urothelial bladder cancer (UBC), a neoplasm where rates of recurrence, progression and platinum-based resistance are generally elevated. We used two muscle-invasive UBC cell lines to study AZD3965 activity regarding lactate production, UBC cells’ viability and proliferation, cell cycle profile, and migration and invasion properties. An “in vivo” assay with the chick chorioallantoic membrane model was additionally performed, as well as the combination of the compound with cisplatin. AZD3965 demonstrated anticancer activity upon low levels of MCT4, while a general lack of sensitivity was observed under MCT4 high expression. Cell viability, proliferation and migration were reduced, cell cycle was arrested, and tumor growth “in vivo” was inhibited. The compound sensitized these MCT4-low-expressing cells to cisplatin. Thus, AZD3965 seems to display anticancer properties in UBC under a low MCT4-expression setting, but additional studies are necessary to confirm AZD3965 activity in this cancer model.
Keywords: AZD3965; lactate; monocarboxylate transporters; urothelial bladder cancer; Warburg effect